(untitled) (Colombia Medica, 1988)
The medical records of 364 patients who underwent surgery for abdominal trauma at the Hospital Universitario del Valle in 1983 were analyzed. Males constituted 88.5% of the cases, and 79.7% of the patients were between 15 and 44 years of age. Open abdominal trauma was found in 78% of the histories; in the rest, there was blunt trauma. A sharp weapon produced open trauma in 66.6% and a bullet in 32%. The clinical assessment of the abdomen was positive in 58% of the cases, doubtful in 21.2%, and negative in 18.4%. The wound was explored locally in 11.6% of the patients; 66 abdominal punctures and 13 peritoneal washings were performed, contrasting with other hospital centers that use peritoneal lavage as the primary diagnostic method in cases of doubtful abdomen. Negative laparotomy rates were 15.1% in blunt trauma, 10.6% in gunshot wounds, and 3.7% in blunt trauma. The sensitivity of the clinical assessment was 83.2%, with a specificity of 89.3%; false positives, 10.7%; and false negatives, 16.8%. The most frequent complication was wound infection. The overall mortality rate was 9.1%.